2012
DOI: 10.1021/ja303618z
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative γ-Addition of Enals to Trifluoromethyl Ketones: Enantioselectivity Control via Lewis Acid/N-Heterocyclic Carbene Cooperative Catalysis

Abstract: An oxidative γ-functionalization of enals under N-heterocyclic carbene (NHC) catalysis to give unsaturated δ-lactones is disclosed. Enantioselectivity control involving the relatively remote enal γ-carbon was achieved via Lewis acid [Sc(OTf)(3) or combined Sc(OTf)(3)/Mg(OTf)(2)] and NHC cooperative catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
150
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 352 publications
(156 citation statements)
references
References 86 publications
1
150
0
4
Order By: Relevance
“…We started by using enal 1a and enone 2a as the model substrates, in the presence of 2 equiv. quinone 4 as an oxidant [29][30][31][32][33] and Cs 2 CO 3 as a base. No formation of the proposed benzene 3a was observed in the absence of an NHC precatalyst (Table 1, entry 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We started by using enal 1a and enone 2a as the model substrates, in the presence of 2 equiv. quinone 4 as an oxidant [29][30][31][32][33] and Cs 2 CO 3 as a base. No formation of the proposed benzene 3a was observed in the absence of an NHC precatalyst (Table 1, entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, addition of the carbene catalyst to the aldehyde moiety of enal followed by deprotonation forms Breslow intermediate I [26][27][28] . This process is followed by oxidative transformation [29][30][31][32][33] , and former enal g-CH deprotonation 33 moiety. Subsequent g-CH deprotonation of IV lead to dienolate intermediate V that undergoes an intramolecular aldol to form a cyclic intermediate VI.…”
mentioning
confidence: 99%
“…2a, while strong bases (such as NaH, KO t Bu, DBU) promote the formation of NHC-Cu complex B from the corresponding triazolium NHC pre-catalyst A and CuI, weak bases (such as TEA, DIEA, K 2 CO 3 ) led to little NHC-Cu complex after several hours. In our prior studies 27,[33][34][35] , it is known that weak bases such as DIEA or K 2 CO 3 are sufficient for the deprotonation of triazoliums to form the carbene catalyst. We therefore concluded that under 'weak' base conditions, there is a controllable kinetic/thermodynamic window that allows the carbene organocatalyst and Cu metal catalyst to co-exist with a meaningful level of concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Several efforts have been directed towards addressing such metal/organic catalysts' quenching issues. These efforts include the use of step-by-step protocols of sequential addition of catalysts 23 , the introduction of additional coordinating ligands to compete with the organocatalysts 24,25 and the use of early transition metals that do not show strong-coordinating properties 26,27 .…”
mentioning
confidence: 99%
See 1 more Smart Citation